Anti-inflammatory and hemostatic effects of Linaria reflexa Desf. Issue 16 (12th August 2021) - Cheriet, Thamere; Hanfer, Mourad; Mancini, Ines; Benelhadj, Samiha; Laouas, Nour Essabah; Ameddah, Souad; Menad, Ahmed; Seghiri, Ramdane
Abstract: The work presented here was aimed to investigate the in vivo anti-inflammatory and in vitro hemostatic activities of Linaria reflexa extract and to establish the relationship between its bioactivity and chemical composition. Twenty-three secondary metabolites were identified, most of them are good anti-inflammatory agents, in line with data by carrageenin-induced rat paw edema assays of the n -butanol extract showing high anti-inflammatory inhibition (63.90%) of edema swelling in the rat paw at the dose 200 mg/kg after 4 h. Furthermore, both extent of inflammatory response and tissue injury were prevented keeping the levels of rate myeloperoxidase (60.16%) and of malondialdehyde, which is the final product of lipid peroxidation generated by free radicals (58.58%). The same extract showed also a remarkable hemostatic effect established by measuring the coagulation time of decalcified plasma (45 s), related to its flavonoid glycosides content. Graphical Abstract: